Artifacts in metallography: stains on the surface of metallographic samples - A. G. Anisovich (Литьë и металлургия)
The article discusses stains from water and reagents, as well as false structures that occur on the surface of metal and alloy samples during metallographic sample preparation and etching. The appearance of such artifacts under bright‑field illumination and when using optical contrasting techniques such as dark‑field and polarized light is demonstrated.